Short-Term Climatic Effect of Gyaring and Ngoring Lakes in the Yellow River Source Area, China - Yang, Xianyu; Wen, Jun; Huang, Anning; Lu, Yaqiong; Meng, Xianhong; Zhao, Yong; Wang, Yurun; Meng, Lixia (Frontiers in Earth Science, 2022)
Based on the field observation and WRF-CLM model, the effects of Gyaring and Ngoring lakes on the short-term climate over the Yellow River source area during May to September have been studied through two experiments with and without the lakes. A backward water vapor transfer model was also employed to investigate the contribution of water vapor evapotranspiration from the Gyaring and Ngoring lakes and various surface types to the local precipitation. The results show that without the Gyaring and Ngoring lakes, the sensible heat is increased by 120%, whereas the latent heat is decreased by 58.5%, and the height of atmospheric boundary layer increases from 500 to 1,500–2,000 m during daytime over the lake area. The sum of sensible and latent heat fluxes in the lake area simulated by the experiment with and without the lakes is 185.8 and 130.3 W m−2, respectively. The precipitation amount over the lake area is significantly increased without considering the lake effect, generally by more than 20–40 mm. About 63.8% of the total precipitation in Gyaring and Ngoring lakes is contributed by the external water vapor sources. The evapotranspiration from the grassland is the secondary water vapor source for the precipitation in the Yellow River source area, and 25.2% of the total precipitation is contributed by this source. Around 4.2% of the total precipitation in the lake area is contributed by the evaporation from the Gyaring and Ngoring lakes.